Advances in atmospheric chemistry Volume 1 - Barker, John Roger; Steiner, A. L. (Allison L.), 1972-; Wallington, Timothy J. (Singapore ; Hackensack, NJ : World Scientific Publishing Co. Pte. Ltd., 2017)
'The human race has altered the chemical composition of the atmosphere, as evidenced by the notorious London smog, photochemical air pollution, acid rain, stratospheric ozone depletion, and elevated greenhouse gas concentrations. The aim of this book series is to present invited summaries of important current research on atmospheric chemistry in a changing world. The summaries range from comprehensive scholarly reviews of major subject areas to more narrowly focused accounts of recent advances by individual research groups. The topics are tied to the important societal issues of air quality, stratospheric ozone depletion, acid deposition, the environmental fate of toxics, and climate change. By gathering these new Advances in one series, we aim to catalyze communication among the many researchers who are studying our changing, contemporary atmosphere.'--Publisher's website.
Title from PDF title page (viewed May 4, 2017).
Includes bibliographical references and index.
Electronic reproduction.
Mode of access: World Wide Web.
Keywords: Atmospheric chemistry; Electronic books